The role of social norms and trust in authority in tax compliance dilemmas - Nur Cahyonowati; Dwi Ratmono; Agung Juliarto (Cogent Business & Management, 2023)
This study aims to examine the effect of economic factors and psychological factors on dilemmas in tax reporting. This study considers psychological factors caused by the inconsistency of the traditional tax compliance model. The economic factors tested are fines and tax audits while the psychological factors tested are trust and social norms. This study applied an experimental method with a 2x2x2 factorial design to investigate tax compliance. The final participants comprise 196 students. The results provide empirical evidence that trust and social norms can be explanatory factors in tax reporting dilemmas. However, this study does not provide empirical evidence regarding the effect of economic factors on tax compliance. The research results imply that the tax authorities need to consider the psychological factors behind taxpayers achieving honesty in tax reporting. This research also has implications in terms of the importance of a comprehensive approach in investigating compliance behavior. Overall, this study contributes to the literature that emphasizes the importance of psychological factors to investigate tax compliance. This study suggests the importance of social norms and trusts to guide behavior in tax compliance dilemmas.
Keywords: 650; social dilemma; social norms; tax compliance; traditional approach; trust